A Tale of Two Hypersecreting Adrenal Neoplasms in the Heartland of COVID-19 Pandemic, Lombardy, Italy - Benedetta Zampetti; Roberto Attanasio; Emanuela Carioni; Daniela Dallabonzana; Iuliana Pauna; Marco Boniardi; Renato Cozzi (Case Reports in Endocrinology)
In this study, we report the management, in Lombardy, Italy, of one patient with Cushing’s syndrome due to adrenal adenoma and another one with pheochromocytoma, whose surgeries were deferred owing to the COVID-19 pandemic.